A study of polar ozone depletion based on sequential assimilation of satellite data from the ENVISAT/MIPAS and Odin/SMR instruments - Rösevall, J. D.; Murtagh, D. P.; Urban, Jakub; Jones, A. K. (CCSD, 2007)
International audience The objective of this study is to demonstrate how polar ozone depletion can be mapped and quantified by assimilating ozone data from satellites into the wind driven transport model DIAMOND, (Dynamical Isentropic Assimilation Model for OdiN Data). By assimilating a large set of satellite data into a transport model, ozone fields can be built up that are less noisy than the individual satellite ozone profiles. The transported fields can subsequently be compared to later sets of incoming satellite data so that the rates and geographical distribution of ozone depletion can be determined. By tracing the amounts of solar irradiation received by different air parcels in a transport model it is furthermore possible to study the photolytic reactions that destroy ozone. In this study, destruction of ozone that took place in the Antarctic winter of 2003 and in the Arctic winter of 2002/2003 have been examined by assimilating ozone data from the ENVISAT/MIPAS and Odin/SMR satellite-instruments. Large scale depletion of ozone was observed in the Antarctic polar vortex of 2003 when sunlight returned after the polar night. By mid October ENVISAT/MIPAS data indicate vortex ozone depletion in the ranges 80?100% and 70?90% on the 425 and 475 K potential temperature levels respectively while the Odin/SMR data indicates depletion in the ranges 70?90% and 50?70%. The discrepancy between the two instruments has been attributed to systematic errors in the Odin/SMR data. Assimilated fields of ENVISAT/MIPAS data indicate ozone depletion in the range 10?20% on the 475 K potential temperature level, (~19 km altitude), in the central regions of the 2002/2003 Arctic polar vortex. Assimilated fields of Odin/SMR data on the other hand indicate ozone depletion in the range 20?30%.